Ebola outbreak 2014-2015: An update - Varun Goel; Tarun Goel; Dinesh Kumar (MAMC Journal of Medical Sciences, 2015)
The 2014–2015 Ebola epidemic is the largest in history, affecting multiple countries in West Africa. In late July 2014, the World Health Organization (WHO) declared the outbreak a Grade 3 emergency, its highest level of any emergency response. In early August, they declared it a public health emergency of international concern, meaning it is a serious public health event that endangers international public health. Indeed, by the end of September 2014, the United Nations stated the outbreak is “a threat to international peace and security.” Guinea located on the Atlantic coast of West Africa, is the first country in this geographical region in which an outbreak of Ebola virus disease has occurred. Cases having been confirmed in other countries include Guinea, Liberia, and Sierra Leone. There were a small number of cases reported in Nigeria and Mali and a single case reported in Senegal; however, these cases were contained with no further spread in these countries. Confirmed imported cases have occurred in the United States, Italy, Spain, and the United Kingdom. The WHO declared the end of the Ebola outbreak in Liberia on May 9, 2015 but on June 29, routine surveillance again detected a new confirmed case of Ebola in Liberia. On November 18, 2014, India has quarantined a man who was cured of Ebola in Liberia. As of August 21, 2015, the cumulative number of probable, suspected, and laboratory-confirmed cases attributed to Ebola virus (EBOV) is 28,036, including 11,301 deaths. Zaire EBOV strain has been identified as causative agent for 2014 Ebola epidemic.